2022
DOI: 10.3389/fphar.2022.820593
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine Citrate Suppresses Breast Cancer via Depletion of Glutathione Peroxidase 4 and Activation of Nuclear Receptor Coactivator 4-Mediated Ferritinophagy

Abstract: Tetrandrine citrate (TetC), a novel tetrandrine salt with high water solubility, demonstrates a potent antitumor activity in chronic myeloid leukemia. Studies have indicated an important role of ferroptosis in breast cancer (BC). However, whether TetC inhibits BC progression via ferroptosis has never been explored. In the present study, we showed that TetC had a significant inhibitory effect on the proliferation and migration of MCF7 and MDA-MB-231 cells. Then, we combined TetC with different inhibitors to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Mortality factor 4 like 1 (MORF4L1) is a part of NuA4 histone acetyltransferase (HAT) complex [31][32][33][34] and as a new BRCA complex-interacting protein, previous studies also identi ed its role in repairing DNA double-strand breaks in BC, revealing its protective role in BC initiation and progression [35][36][37][38]. Nuclear receptor coactivator 4 (NCOA4) is normally known as its function in mediating ferritinophagy [39,40] and recent research also shows its potential function in immune arousal of BC [41]. Moreover, the presence of NCOA4-rearranged during transfection (RET), one of the initial detections with oncogenic RET gene fusions, is proved to result in relative resistance to treatment with trastuzumab and pertuzumab in BC with ER+/ERBB2 ampli cation positive for NCOA4-RET fusion [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality factor 4 like 1 (MORF4L1) is a part of NuA4 histone acetyltransferase (HAT) complex [31][32][33][34] and as a new BRCA complex-interacting protein, previous studies also identi ed its role in repairing DNA double-strand breaks in BC, revealing its protective role in BC initiation and progression [35][36][37][38]. Nuclear receptor coactivator 4 (NCOA4) is normally known as its function in mediating ferritinophagy [39,40] and recent research also shows its potential function in immune arousal of BC [41]. Moreover, the presence of NCOA4-rearranged during transfection (RET), one of the initial detections with oncogenic RET gene fusions, is proved to result in relative resistance to treatment with trastuzumab and pertuzumab in BC with ER+/ERBB2 ampli cation positive for NCOA4-RET fusion [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The shRNA sequence for RELA was GCCTTAATAGTAGGGTAAGTT, and the shRNA sequence for SPARC was CCTAGACAACGACAAGTACAT. A citrate concentration of 10 mmol·L −1 was selected for our in vitro experiments and 30 mg·kg −1 ·day −1 for the in vivo experiments, consistent with previous studies [42,43].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, one study found that Ketamine inhibit the expression of GPX4 by attenuating KAT5 on the promoter region of GPX4, repressing the enrichment of histone H3 lysine 27 acetylation and RNA polymerase II ( Li H. et al, 2021 ). Some other small molecule compounds ( Table 2 ) such as alloimperatorin ( Zhang J. et al, 2022b ), tetrandrine citrate ( Yin et al, 2022 ), pyrrolidin-3,2′-oxindoles ( Liu S.-J. et al, 2021 ), Saponin Formosanin C ( Chen H.-C. et al, 2022 ) can also induce ferroptosis in breast cancer cells by interfering with the System X c − /GSH/GPX4 axis.…”
Section: Potential Roles Of Targeting System X C ...mentioning
confidence: 99%